The Effects of Monaural Beat Technology on Learners' Experiences of Music Performance Anxiety (MPA) - Flanagan, Jayson Edward (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
Music performance anxiety (MPA) is related to the experience of persisting, distressful, apprehensions about and/or actual impairment of performance skills in a public context, to a degree unwarranted given the individual's musical aptitude, training and level of preparation (Salmon 1990). This research project set out to investigate learners' subjective experiences of the effects of monaural beat (MB) vibrational frequencies on their experiences of MPA. The research project was a qualitative study based on a phenomenological research paradigm, which fundamentally aims to explore an experience in its own terms (Smith et al. 2009). The research participants consisted of four subject music pupils at St Andrew's College and The Diocesan School for Girls and were interviewed through in-depth, semi-structured interviews over two practical examinations. The results suggested that various factors contribute to the experience of music performance anxiety, such as the performers' perceptions of audience reactions, as well as the context of the performance. Self-esteem and the performer's fragile sense of self-worth and self-confidence also play an important role in influencing their music performance anxiety. However, listening to monaural beats during a performance has the ability to lower levels of music performance anxiety by eliciting the following effects: an improved sense of confidence within the listeners; a sense of calm; the monaural beats working on a passive awareness level that allows the beat to operate at a sub-conscious level; the ability to focus better on the task at hand as well as benefit the listener in non-musical contexts such as studying; general concentration or ordinary tasks such as gardening or going for a run. The research suggests that listening to monaural beats during a musical performance can benefit the performer by lowering levels of MPA. As a result, the performer will experience an improved sense of confidence, calmness and the ability to focus better on the task at hand. Monaural beats have also shown to be a useful method of dealing with MPA instead of resorting to pharmaceutical drugs or other methods of coping such as playing games for distraction.
Keywords: Performance anxiety Alternative treatment; School music -- South Africa -- Makhanda; Music students -- South Africa -- Makhanda Examinations; Beats (Acoustics) Psychological aspects; Monaural Beat Technology